1999
DOI: 10.1242/dev.126.23.5431
|View full text |Cite
|
Sign up to set email alerts
|

Pollen-stigma adhesion inArabidopsis:a species-specific interaction mediated by lipophilic molecules in the pollen exine

Abstract: To investigate the nature and role of cell adhesion in plants, we analyzed the initial step of pollination in Arabidopsis: the binding of pollen grains to female stigma cells. Here we show this interaction occurs within seconds of pollination. Because it takes place prior to pollen hydration, it also requires adhesion molecules that can act in a virtually dry environment. We developed assays that monitored adhesion of populations of pollen grains and individual cells. Adhesion between pollen and stigma cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(38 citation statements)
references
References 37 publications
0
38
0
Order By: Relevance
“…This is somewhat similar to the de novo contacts of pollen grains to the female stigma cells which was reported to be governed possibly by specific interactions involved the lipophilic molecules on the pollen exine. 57 …”
Section: Resultsmentioning
confidence: 99%
“…This is somewhat similar to the de novo contacts of pollen grains to the female stigma cells which was reported to be governed possibly by specific interactions involved the lipophilic molecules on the pollen exine. 57 …”
Section: Resultsmentioning
confidence: 99%
“…This appressorium-like 'foot' appears to glue the pollen to the stigma, after which hydration takes place [8,20]. In Arabidopsis, it has been shown that the strength of pollen adhesion is directly proportional to the genetic distance between species [34]. In our intertribal crosses, this pollen-pistil interaction was showing no abnormalities, resulting in pollen adhesion, hydration, germination and pollen tube penetration into the stylar tissue.…”
Section: Discussionmentioning
confidence: 59%
“…In Anemone and Ranunculus, the stigma is typically dry papillated [19]. As dry stigmas do not produce exudates, pollen adhesion is largely realized by the properties of the pollen surface [34]. Adhesion relies on the interaction between pollen coat proteins and receptors in the stigma [10].…”
Section: Discussionmentioning
confidence: 99%
“…In flowering plants, the pollen wall is important for the success of sexual reproduction as it both protects the microgametophyte from various biotic and abiotic stresses, and also functions in cell–cell recognition during pollination ( Zinkl et al, 1999 ; Edlund et al, 2004 ). In Arabidopsis, the mature pollen wall has an intricate multi-layered structure, including the intine, exine, and tryphine ( Owen and Makaroff, 1995 ; Yue et al, 2014 ; Shi et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%